Attention-deficit/hyperactivity Disorder (ADHD) Symptoms, Craving to smoke, and Tobacco Withdrawal Symptoms in Adult Smokers with ADHD - Berlin, Ivan (2012)
BACKGROUND: Tobacco withdrawal symptoms may be confounded with attentiondeficit/ hyperactivity disorder (ADHD) symptoms among smokers with ADHD. OBJECTIVE: 1) to assess overlap between ADHD symptoms and tobacco/nicotine withdrawal symptoms and craving; 2) to assess the relationship between craving or withdrawal symptoms and the effect of osmotic-release oral system methylphenidate (OROS-MPH) on ADHD symptoms; 3) to assess the association of ADHD symptoms, craving, and withdrawal symptoms with abstinence. METHODS: Secondary analysis of a randomized, placebo controlled smoking cessation trial assessing the efficacy of OROS-MPH taken in addition to nicotine patch among individuals with ADHD. ADHD symptoms, withdrawal symptoms, and craving were assessed at baseline and 2, 4 and 6 weeks after a target quit day. RESULTS: Withdrawal symptoms and craving showed limited and modest overlap with ADHD symptoms prior to abstinence but more extensive and stronger correlation after quit day. Compared to placebo, OROS-MPH reduced ADHD symptoms; this effect was attenuated by controlling for withdrawal symptoms, but not by craving. Craving, but not ADHD symptoms and withdrawal symptoms, was associated with abstinence during the trial. CONCLUSION: When treating smokers with ADHD 1) craving, rather than tobacco withdrawal symptoms or ADHD symptoms may be the more effective therapeutic smoking cessation targets; 2) careful distinction of craving, withdrawal symptoms, and ADHD symptoms when assessing withdrawal phenomena is needed.